Nondestructive Controllable Grouting: A Novel Method to Correct Deviation of Building Foundation - Xuedong Cui (Advances in Civil Engineering)
Nondestructive controllable grouting is a novel method for the accurate, reliable, and nondestructive lifting of buildings. In this method, the grouting construction is divided into several stages. First, a shallow soil layer is gradually filled and compacted by grouting, and the deep soil is reinforced by grouting until a radial compression force is generated. Subsequently, fracture grouting is performed in the middle of the reinforcement area, which generates a lifting force and resulting in the uplift of the building. Surface deformation monitoring is used during the entire uplifting process to control the amount of uplift. This method has been verified through the construction of a residential building, and the results show that nondestructive controllable grouting can effectively solve the problem of building deflection. At the same time, it avoids the problem of excessive lifting or secondary settlement that may occur in traditional grouting reinforcement. This study is expected to have considerable value as a reference for the construction of similar projects.